Expectation horizons; readers and followers of Euclides da Cunha in the pages of the Tapejara newspaper in Ponta Grossa, 1952 (Revista de História Regional, 2008)
This article tries to understand the readings ofEuclides da Cunhas Os Sertões, which the members of theCentro Cultural Euclides da Cunha, in Ponta Grossa, inSouthern Brazil, did along the 1940s and 50s. The analysisis centered on the different understandings of Braziliannationality, regional identities, and gathering around theideals of race, nation and literature in order to form aninterpretative community which shared the representationsabout these themes.